Recent Advances in the Reutilization of Granite Waste in Various Fields (Journal of Material Science and Technology Research, 2021)
Quarrying and processing of granite produce large amounts of waste residues. Besides being a loss of resources, improper disposal of these wastes results in pollution of the soil, water and air around the dumpsites. The main components of granite waste are quartz, feldspars and a small amount of biotite. Due to its hard and dense texture, high strength, corrosion resistance and wear resistance, granite waste may be recycled into building materials, composite materials and fine ceramics, effectively improving their mechanical properties and durability. By using the flotation process, high value-added products such as potash feldspar and albite may be retrieved from granite waste. Also, granite waste has the potential for application in soil remediation and sewage treatment. This review presents recent advances in granite waste reutilization, and points out the problems associated with its use, and the related countermeasures, indicating the scale of high value-added reutilization of granite waste.